2018
DOI: 10.1136/bcr-2017-222269
|View full text |Cite
|
Sign up to set email alerts
|

Cutis marmorata telangiectatica congenita and major lower limb asymmetry

Abstract: A 39-week-old male newborn presented at birth with atrophic erythematous and purpuric skin lesions, in a typical right-sided segmental distribution. Lesions were persistent and unaffected by rewarming in the postpartum period. Postnatal echocardiogram showed a predominance of the right cavities and an upper atrial septal defect. Cerebral and abdominal ultrasound were normal along with ophthalmological examination. On follow-up, lower limbs asymmetry was noted. The right lower limb was shorter in length and had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…In our case, the patient had hypoplasia of toes with greater affliction for the lateral toes. Other has found that there was lower limb-length discrepancy of 1.5 cm without hypoplasia of toes (Amaral et al, 2018). Our case had hypoplasia of toes without limb-length discrepancy.…”
Section: Sirsupporting
confidence: 48%
“…In our case, the patient had hypoplasia of toes with greater affliction for the lateral toes. Other has found that there was lower limb-length discrepancy of 1.5 cm without hypoplasia of toes (Amaral et al, 2018). Our case had hypoplasia of toes without limb-length discrepancy.…”
Section: Sirsupporting
confidence: 48%
“…Of 51 patients originally classified as CMTC in our patient databases, 31 met our clinical definition and were thus also included (Figure 1). 16–57 …”
Section: Resultsmentioning
confidence: 99%
“…The circumference of the right thigh (22.5 cm versus 21 cm) and the right leg (17 cm versus 15 cm) was greater than their counterparts. In 2018, Amaral et al reported a 39-week-old male infant who presented at birth with cutis marmorata telangiectatica congenita in a typical right-sided segmental distribution [ 21 ]. At 6 months of age, the right lower limb was 1.5 cm shorter than the left lower limb and had a smaller diameter.…”
Section: Discussionmentioning
confidence: 99%